2016
DOI: 10.3389/fpls.2016.01664
|View full text |Cite
|
Sign up to set email alerts
|

Rhizosphere Organic Anions Play a Minor Role in Improving Crop Species' Ability to Take Up Residual Phosphorus (P) in Agricultural Soils Low in P Availability

Abstract: Many arable lands have accumulated large reserves of residual phosphorus (P) and a relatively large proportion of soil P is less available for uptake by plants. Root released organic anions are widely documented as a key physiological strategy to enhance P availability, while limited information has been generated on the contribution of rhizosphere organic anions to P utilization by crops grown in agricultural soils that are low in available P and high in extractable Ca, Al, and Fe. We studied the role of rhiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 59 publications
4
50
0
2
Order By: Relevance
“…Despite the importance of oats, limited research has been carried out on its adaptation to P starvation, and particularly the molecular regulation of root and root-released organic anions in response to P deficiency. In a previous report, we found that oat showed an increased root mass / total biomass ratio, high percentage of root colonization by arbuscular mycorrhizal fungi (AMF), large amounts of rhizosphere organic anions and efficient P uptake in low P availability soils (Wang et al , 2016). These findings paved the way for our current study on the molecular mechanisms underlying P deficiency responses in oat roots and the genes and metabolites involved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the importance of oats, limited research has been carried out on its adaptation to P starvation, and particularly the molecular regulation of root and root-released organic anions in response to P deficiency. In a previous report, we found that oat showed an increased root mass / total biomass ratio, high percentage of root colonization by arbuscular mycorrhizal fungi (AMF), large amounts of rhizosphere organic anions and efficient P uptake in low P availability soils (Wang et al , 2016). These findings paved the way for our current study on the molecular mechanisms underlying P deficiency responses in oat roots and the genes and metabolites involved.…”
Section: Introductionmentioning
confidence: 99%
“…Plants have evolved various adaptive strategies to cope with P deficiency in nature. Examples are morphological responses such as changes in root architecture (Hermans et al , 2006; Lynch, 2011); physiological adaptations like secreted organic anions and acid phosphatases (Cheng et al , 2014; Gahoonia et al , 2000; Hedley et al , 1982; Hoffland et al , 1989; Jones 1998; Lambers et al , 2006; Pang et al , 2015; Ryan et al , 2001; Wang et al , 2016), biochemical responses to optimize utilization of internal P such as replacement of P-lipids with non-P lipids (Chiou & Lin, 2011; Faucon et al , 2015; Lambers et al , 2015; Plaxton & Tran, 2011;), and molecular responses like induced expression of high-affinity phosphate transporters (Wu et al , 2013; Zhang et al , 2014). In addition, for plant species that are capable of interacting with mycorrhizal fungi, P uptake by the mycorrhizal hyphae is the dominant pathway for P acquisition (Smith et al , 2003; Sawers et al , 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Lu et al [33] identified a novel secreted purple APase in rice (OsPAP10c) and investigated its role in organic P utilization -OsPAP10c overexpression significantly increased APase activity both in leaves and roots, but especially on the root surface and in culture media. Studies by Wang et al [47] indicated that the quantity of rhizosphere APase had positive correlations with P fractions available to plants and Pi uptake by the plants in low-Pi soils; these authors also stated that both Brassica napus and Avena sativa were good candidates to study P utilization.…”
Section: Modification Of Acid Phosphatase Activity and Localization Amentioning
confidence: 99%
“…However, the decrease of pH in the nutrient media (and rhizosphere) was not observed in our experimental conditions (data not shown) [49], which suggested that oat plants did not respond to Pi starvation via increased exudation of protons or organic acids from the roots. Wang et al [47] suggested that the effects of organic anions in the rhizosphere varied among the plant species and these exudates appeared to play minor roles in improving Pi uptake and the availability in soil.…”
Section: Modification Of Acid Phosphatase Activity and Localization Amentioning
confidence: 99%
“…All plant nutrients other than nitrogen were provided as follows, in mg kg -1 soil: P, 41.5; K, 70.2; Mg, 9.6; Fe, 5.6; Mn, 1.1; Cu, 0.32; Mo, 0.48; B, 0.11; Zn, 0.65. The addition of these nutrients limits their effect on plant growth (Wang, 2016).…”
Section: Soil Preparationmentioning
confidence: 99%